Padrão de sensibilidade aos antimicrobianos de bacilos gram-negativos não fermentadores isolados de materiais clínicos de pacientes em Presidente Prudente - SP - Tumitan, A. R P; Pizzolitto, Antonio Carlos [UNESP] (My University, 2004)
The aim of this study was the assessment of isolation frequency and antimicrobial susceptibility pattern of nonfermenting Gram-negative bacilli. Ninety eight strains of nonfermenting Gram-negative bacilli, isolated from several clinical materials of patients admited at the Dr. Domingos Leonardo Cerávolo University Hospital and at Dr. Odilo Antunes Siqueira State Hospital, as well as from every outpatient; assisted at Laboratory of Clinical Analysis of Unoeste University, Presidente Prudente, São Paulo, in the period of October 1999 to April 2001 were analyzed. The most frequent species were Pseudomonas aeruginosa (65.3%) and Acinetobacter baumannii (23.5%). The frequency of the other isolated species was smaller than 2.5%. In the antimicrobial susceptibility tests, the two species more prevalent showed high resistance. The antibiotic most active in vitro was the imipenem, with 79.6% in microdiluition method, and 76.6% in diffusion method, for Pseudomonas aeruginosa strains and 100.0% in both microdiluition and diffusion methods, for Acinetobacter baumannii. The cephalosporins of third generation, the ciprofloxacin and the aminoglycosides, presented percentage of susceptibility varying from 22.4 to 69.7%. These results bring implications to the emergency use of the antimicrobial agents in the treatment of patients with severe infection.
Susceptibility pattern to the antimicrobial agents of nonfermenting Gram-negative bacilli isolated from clinical materials of patients at Presidente Prudente-SP
Keywords: Acinetobacter baumannii; Antimicrobial susceptibility; Nonfermenting Gram-negative bacilli; Nosocomial infection; Pseudomonas aeruginosa; amikacin; aminoglycoside; ampicillin; antibiotic agent; aztreonam; cefalotin; cefepime; cefotaxime; ceftazidime; ceftriaxone; cefuroxime; cephalosporin derivative; ciprofloxacin; doxycycline; gentamicin; imipenem; levofloxacin; lomefloxacin; nalidixic acid; norfloxacin; ofloxacin; piperacillin; piperacillin plus tazobactam; sulfazotrim; tetracycline; timentin; tobramycin; unclassified drug; antibiotic resistance; antibiotic sensitivity; bacterium isolation; diffusion; Gram negative bacterium; nonhuman; university hospital